Obesity, Visceral Fat, and NAFLD: Querying the Role of Adipokines in the Progression of Nonalcoholic Fatty Liver Disease. (26th May 2011) - Mirza, M. S.
Abstract : Nonalcoholic fatty liver disease (NAFLD) represents a spectrum of clinicopathologic conditions ranging from steatosis alone to nonalcoholic steatohepatitis (NASH), with varying risks for progression to cirrhosis and hepatocellular carcinoma. There is mounting evidence that NAFLD not only complicates obesity, but also perpetuates its metabolic consequences. Critical event that leads to progressive liver injury in NAFLD is unknown. Obesity reflects a generalized proinflammatory state with its increased inflammatory markers like C reactive protein, IL-6, IL-8, IL-10, PAI-1, TNF- α, and hepatocyte growth factor. The elevated production of these adipokines is increasingly considered to be important in the development of diseases linked to obesity and the metabolic syndrome. Disordered cytokine production is likely to play a role in the pathogenesis of NAFLD. There is no effective treatment for NAFLD, though weight loss may halt disease progression and revert histological changes, the underlying mechanism remaining elusive. All stages of the disease pathway from prevention, early identification/diagnosis, and treatment require an understanding of the pathogenesis of liver injury in NAFLD.